2017
DOI: 10.1007/s12149-017-1218-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sequential SPECT and CT for targeted radionuclide therapy dosimetry

Abstract: We conclude that if both sequential SPECT/CT scans are available, CT organ-based registration method can more effectively improve the 3D dose estimation. Sequential low-dose CT scans might be considered to be included in the standard TRT protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Integrated CT in SPECT/CT can be used for attenuation correction (AC) in SPECT reconstruction to improve quantitative accuracy, and provide anatomical reference for the activity uptakes in general. For TRT dosimetry, CT data can be further used in segmentations of tumors and critical organs, or registrations to reduce the misalignments among serial scans [4,5]. However, the accuracy of registration between SPECT and CT data is limited by certain voluntary and involuntary motion since CT scans take couple seconds while SPECT imaging needs at least several minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Integrated CT in SPECT/CT can be used for attenuation correction (AC) in SPECT reconstruction to improve quantitative accuracy, and provide anatomical reference for the activity uptakes in general. For TRT dosimetry, CT data can be further used in segmentations of tumors and critical organs, or registrations to reduce the misalignments among serial scans [4,5]. However, the accuracy of registration between SPECT and CT data is limited by certain voluntary and involuntary motion since CT scans take couple seconds while SPECT imaging needs at least several minutes.…”
Section: Introductionmentioning
confidence: 99%
“…For vCT and rCT protocols, first we semi‐automatically segmented the target organs, that is, liver, spleen, kidneys, and lungs at all time points on respective vCTs and rCTs images. We then applied organ‐by‐organ nonrigid registration . For the conventional 1CT protocol, as some organ‐of‐interest regions cannot be delineated from SPECT images at later time points, whole‐body SPECT registrations were performed while the single CT was used for organ segmentation.…”
Section: Methodsmentioning
confidence: 99%
“…However, SPECT images have relatively poor resolution, high noise levels, and insufficient anatomical information, leading to large uncertainties for image registration and segmentation . Previously, we showed that the use of sequential computed tomography (CT) images for nonrigid registration is superior to sequential SPECT in 3D TRT dosimetry . Nonetheless, CT‐aided dosimetry does require good alignment between SPECT and CT images at each time point.…”
Section: Introductionmentioning
confidence: 99%
“…However, non-rigid registration based on whole body images is relatively computational intensive. Previously, we proposed that organ-based non-rigid registration on sequential quantitative SPECT or CT images can improve the dosimetric estimation (24,25). On the other hand, we also developed a virtual CT (vCT) method to generate CT at different time points when only a single CT is available in the sequential imaging protocol to sustain the dose calculation accuracy (26).…”
Section: Introductionmentioning
confidence: 99%